2000
DOI: 10.1067/mva.2000.103788
|View full text |Cite
|
Sign up to set email alerts
|

Vascular smooth muscle cell effect on endothelial cell endothelin-1 production

Abstract: Endothelin-1 (ET-1) is a potent mitogen secreted by endothelial cells (ECs) in culture and is a putative factor in vascular lesion development. The purpose of this study was to examine whether smooth muscle cells (SMCs) inhibit EC secretion of ET-1. The effect of SMCs on EC ET-1 and constitutively expressed nitric oxide (NO) synthase activity was examined by using a bilayer co-culture model. SMCs inhibited both EC ET-1 protein and RNA levels, compared with ECs cultured alone. SMCs increased EC NO production wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2001
2001
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(20 citation statements)
references
References 26 publications
0
19
0
Order By: Relevance
“…2,13,16,20 Studies in arterial intimal hyperplasia following vascular injury have demonstrated that SMC inhibit EC secretion of endothelin (ET-1), a potent SMC mitogen, by increasing the activity of eNOS and increasing NO concentration in the EC/SMC microenvironment. 9 In modules seeded with HUVEC (with or without UVSMC), the secretion of NO decreased over time (14 days). This may be due to the proliferation 5 and migration of seeded HUVEC over the time span.…”
Section: Effect Of Embedded Uvsmc On Huvec Phenotypementioning
confidence: 99%
See 1 more Smart Citation
“…2,13,16,20 Studies in arterial intimal hyperplasia following vascular injury have demonstrated that SMC inhibit EC secretion of endothelin (ET-1), a potent SMC mitogen, by increasing the activity of eNOS and increasing NO concentration in the EC/SMC microenvironment. 9 In modules seeded with HUVEC (with or without UVSMC), the secretion of NO decreased over time (14 days). This may be due to the proliferation 5 and migration of seeded HUVEC over the time span.…”
Section: Effect Of Embedded Uvsmc On Huvec Phenotypementioning
confidence: 99%
“…31 Using the same co-culture system, this group also demonstrated that endothelin-1 (ET-1) secretion by EC was inhibited by SMC through its modulation of endothelial nitric oxide synthase (eNOS) activity. 9 On the other hand, an increase in eNOS activity inhibits SMC proliferation and prevents hyperplasia. 18 In both conditioned medium and a transwell system 10 proliferating EC have been shown to enhance the growth of SMC.…”
Section: Introductionmentioning
confidence: 99%
“…These data are not surprising, because endothelin-1 is not able to inhibit basal nitric oxide production, whereas nitric oxide can inhibit endothelin-1 activity on internal mammary arteries and decrease endothelin-1 production in smooth muscle cell. This effect seems mediated through endothelin-B receptor activity [17,40,57].…”
Section: Similarities and Differences Between Cardiac Andmentioning
confidence: 99%
“…These data are not surprising, because endothelin-1 is not able to inhibit basal NOx production, 34 whereas NO can inhibit the vasoconstrictive effects of endothelin-1 on internal mammary arteries 35 and decrease endothelin-1 production in smooth muscle cells. 36 In addition, basal NO production can modulate endothelin-1 activity through endothelial endothelin-B receptor activity. 37 Influence of L-Arginine on Insulin-Stimulated Endothelial Function L-Arginine infusion induced important changes in insulininduced NOx, cGMP and endothelin-1 release in patients with CSX.…”
Section: Piatti Et Al L-arginine In Cardiac Syndrome X 433mentioning
confidence: 99%